Children's Early Reading Ability Through Make-A-Match Based Number Card Play Activities - Ariyani Ariyani; Apon Apon (Universitas Negeri Makassar, 2022)
The purpose of this study was to examine the influence of playing number cards in improving children's initial reading ability based on making a match with a total sample of 20 children. The research uses a quantitative approach with a pre-experimental type of research using one group pretest-posttest design. Based on the research results, the use of number cards improves children's early reading ability. The results of this increase can be seen in the average value of the indicators used, namely distinguishing words and distinguishing sounds/letters at the time of pretest is 2.05, and the percentage of learning completion is 33%. in the posttest there was an increase of 3.65 and learning completion was achieved for all children. This is because in carrying out word card-playing activities, teachers run well according to the stages of playing word cards and learning scenarios that have been prepared.